Mr. Isaac, Dancing-Master - Thorp, Jennifer (Edinburgh: Edinburgh University Press, 2006)
RESUMEN: This article discusses various aspects of the career of Mr. Isaac, the late seventeenth- and early eighteenth-century dancing-master who produced dances of such quality that they still pose remarkable challenges to dancers working on them today. Firstly, it discusses his career in London, with particular reference to new information which has emerged concerning his status as dancing-master to Lord Delamere's young cousin, Katherine Booth; secondly, it considers the extant dances by Mr. Isaac, for their unique choreographic style and their dissemination through the publications of Weaver, Walsh and Pemberton; and thirdly, it explores the possible identity of Mr. Isaac by reviewing the available biographical evidence.